THE EFFECT OF AUDIT FEE AND AUDIT EFFORT ON AUDIT QUALITY (IN MANUFACTURING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE 2017-2019) - Maulia Aurel Salim; Surya Raharja (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of audit fee and audit effort on the audit quality of manufacturing companies in Indonesia. The independent variables in this study are Audit Fee and Audit Effort. Meanwhile, the Audit Quality is a dependent variable depending on its measurement using dummy variable of Big Four and Non-Big Four.The results of this study will show whether audit fee and audit effort have an effect on increasing or decreasing audit quality. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2017-2019. The sampling method used in this study was the purposive sampling method with predetermined criteria to produce 180 samples of manufacturing companies to be studied. The data used are secondary in the form of financial reports and company annual reports obtained through the website www.IDX.co.id and financial information from the Bloomberg terminal. The research was tested using the logistic regression analysis using SPSS 21 software.The results of this study indicate that audit fee has a positive and significant effect on the audit quality. Then the effect of audit effort has no effect on the audit quality.